Integrated noxious weed management plan: U.S. Air Force Academy and Farish Recreation Area - Smith, Pam, author; Panjabi, Susan Spackman, author; Handwerk, Jill, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2015)
The purpose of this plan is to provide a guide to manage, in the most efficient and effective manner, the noxious weeds on the US Air Force Academy (Academy) and Farish Recreation Area (Farish) over the next 10 years (through 2025) This plan pertains to the "natural" portions of the Academy and excludes highly developed areas, such as around buildings, recreation fields, and lawns. This plan covers the entire Farish site, including the developed areas.
Keywords: botany; conservation planning; invasive species